The Effect of Spiritual Leadership and Psychological Empowerment on Employee Performance - Arivatu Ni'mati Rahmatika; Samsul Ma'arif; Siti Kholifah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article aimed to examine and analyze the effect of Spiritual Leadership and Psychological Empowerment on Employee Performance. Respondents were leaders or employees at YPPBU (Bahrul Ulum Islamic Boarding School Foundation) Jombang, totalling 64 respondents. Data were analyzed using Partial Least Square (PLS) with SmartPLS software version 3.0 and the relationship between variables. The results showed that Spiritual Leadership had no significant effect on Employee Performance (T Statistics: 0.925, P Values: 0.355). Psychological Empowerment has a considerable impact on Employee Performance (T statistic: 7,790, P Values: 0.000). Spiritual Leadership has a significant effect on Psychological Empowerment (T Statistics: 6,531, P Values: 0.000). Furthermore, Spiritual Leadership and Psychological Empowerment have no specific considerable impact on Employee Performance (T Statistics: 3,966, P Values: 0.000). Psychological Empowerment has a mediating role on Spiritual Leadership to Employee performance. The Spiritual Leadership and Psychological Empowerment felt by YPPBU's Leaders or Employees are directly proportional to the resulting performance. Changes in Spiritual Leadership and Psychological Empowerment will also affect Employee Performance.